Geographic variation in tobacco use in India: a population-based multilevel cross-sectional study. Issue 6 (21st June 2020) - Singh, Ankur; Arora, Monika; Bentley, Rebecca; Spittal, Matthew J; Do, Loc G; Grills, Nathan; English, Dallas R
Abstract : Objective: This study aims to quantify the extent to which people's use of tobacco products varies by local areas (city ward and village) across India and the variation in this clustering by tobacco products. Design: Cross-sectional study. Setting and participants: Data on 73 954 adults across 2547 city wards and villages were available for analysis from 30 states and 2 union territories in India. Primary and secondary outcome measures: We included as primary outcomes self-reported any tobacco use, current cigarette smoking, current bidi smoking, current smokeless tobacco use and a derived variable for dual use describing respondents who engaged in both smoking and smokeless tobacco use. Results: The median risk of an individual using tobacco was 1.64 times greater if a person hypothetically moved from an area of low to high risk of tobacco use (95% CI: 1.60 to 1.69). Area-level partitioning of variation differed by tobacco product used. Median ORs ranged from 1.77 for smokeless tobacco use to 2.53 for dual use. Conclusions: Tobacco use is highly clustered geographically in India. To be effective in India, policy interventions should be directed to influence specific local contextual factors on adult tobacco use. Where people live in India influences their use of tobacco, and this association may be greater than has been observed in other settings. Tailoring tobacco control policies for local areas in India may, therefore, provide substantial public health benefits.